UPAYA MENINGKATKAN MOTIVASI BELAJAR MAHASISWA DALAM PEMBELAJARAN PEMILIHAN BAHAN DAN PROSES DENGAN METODE TANYA JAWAB DISERTAI PENGHARGAAN - AK, Tri Bambang (Parameter, 2015)
This research aims to enhance learning motivation, material selection and student’s process of Education, Program Study of Mechanical Engineering, second semester in 2006/2007 of academic year, Department of Mechanical Engineering, Faculty of Engineering, State University of Jakarta, by using question and answer method with reward. Used kind of research is class action research. This research uses two cycles preceded by preliminary research. Both these cycles, each consisting of four stages, namely: planning, implementation, observation and reflection. Conducted action taken is by providing rewards for student participation in learning activities. Awards given to each of cycles are different, in the first cycle the awards given are additional value, meanwhile on the second cycle are certificate. Awards obtained from scoring on the observed activity. Application of the method of conversation with rewards obtained there is increasing of learning activity significantly, students become more active and the situation of learning more dynamic and fun. Increasing of student motivation is also indicated by an increase in the value of the test cycle. The average value of the introduction is 4.22 increasing at cycles I to 5.64. Meanwhile, to increase the second cycles to 7.02. beginning by the execution of this research, the use of learning methods of material selection and appropriate process is necessary in order to create a dynamic learning activities and conducive, so it is expected to get better learning results.